Instantaneous frequency measurement of dissipative soliton resonant light pulses - Cuadrado Laborde, Christian Ariel (2016)
We measured the instantaneous frequency profile of two different dissipative soliton resonant (DSR) light pulses, the usual flat-top and less-common trapezoid-shaped light pulses. The DSR light pulses were provided by an ytterbiumdoped polarization-maintaining fiber ring passively modelocked laser using the adequately selected amount of net-normal dispersion. We confirmed that the DSR light pulses have a (moderately) low linear chirp across the pulse, except at the edges, where the chirp changes exponentially. This unique instantaneous frequency behavior can be succinctly resumed by the following parameters: linear chirp slope and leading and trailing chirp lifetimes. As the pump power increases, the linear chirp slope decreases, whereas the leading and trailing chirp lifetimes do not show an appreciable change. The results are compared with previous theoretical works.